Converging Disciplines A Transdisciplinary Research Approach to Urban Health Problems - Kirst, Maritt; Schaefer-McDaniel, Nicole; Hwang, Stephen; O'Campo, Patricia; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Converging Disciplines: A Transdisciplinary Research Approach to Urban Health Problems Maritt Kirst, Nicole Schaefer-McDaniel, Stephen Hwang, and Patricia O$1 (BCampo Centre for Research on Inner City Health, Toronto, Canada As urban populations grow, new health problems evolve in tandem with longstanding issues. And as a welter of social, environmental, and access factors further complicate the picture, workable solutions require increasingly sophisticated understanding and innovative methods$1 (Bgenerally beyond the scope of one professional field. Converging Disciplines introduces the concept of transdisciplinary research as a multidimensional, research-to-practice approach to urban health issues, not only bringing researchers together but also linking stakeholders, from practitioners to policymakers to community members. This immediately accessible volume differentiates transdisciplinary research from multi- and interdisciplinary strategies, as well as from popular community-based models, and brings a uniquely North American set of perspectives to the concept. Chapter authors explore the theory behind the methods as well as their application in meeting chronic problems (e.g., domestic violence, substance abuse) and working with vulnerable populations (e.g., homeless individuals, refugees) in ways that are ecologically based, ethically sound, and eminently practical. Key areas of coverage: Benefits and challenges of transdisciplinary research in the urban health setting. Transdisciplinary research process, including methodologies, collaboration, and information sharing. Detailed case examples of transdisciplinary research used in addressing health issues among marginalized urban populations. An overview of training programs in the U.S. and Canada. The view from funding agencies. Preparing the university, researchers, and the job market for a transdisciplinary future. Researchers and graduate students in urban and public health will find inspiring reading in Converging Disciplines: a bold framework for transforming their fields, and the tools for meeting the new generation of urban health challenges.s
Part I: An Introduction to Transdisciplinary Research -- Introducing Transdisciplinary Research -- The Contributions of Transdisciplinary Research for Urban Health Researchers -- Part II: Examples of Transdisciplinary Research -- Case Example 1 -- Case Example 2 -- Case Example 3 -- Part III: The Process of Transdisciplinary Research -- Methodological Notes on Conducting Transdisciplinary Research -- Process and Collaboration in Transdisciplinary Research -- The Role of Knowledge Translation -- Part IV: Moving Forward -- Training Researchers in Transdisciplinary Research -- Funding Agencies and Transdisciplinary Research -- Moving Forward: The Future of Transdisciplinary Research.
Keywords: Medicine; Medicine & Public Health; Medicine/Public Health, general